Deskripsi ulang dan sarang Bulbitermes germanus (Haviland) (Isoptera: Termitidae) di Indonesia - Syaukani Syaukani (Perhimpunan Entomologi Indonesia, 2017)
Bulbitermes is one of the endemic genera distributed in the Oriental Regions. Information on taxonomy and its nesting biology is very limited compared to other genera in the region. Bulbitermes germanus collected from Indonesia was rediscribed. It was found that color, head capsule contriction and, segmentation antenna are important characters for soldier caste, while antennal segmentation and mandibles conditions (worker caste) determined characters for reducing intra-specific variation within genus. Examination of a large number of colonies from various habitats in Indonesia showed that combination both soldier and worker characters were much efective for systematic work for the species. Colony of this species were relatively abundant in the tropical forests of Sumatra, Borneo, Java, and Papua respectively. Nesting strategies of the species was first time reported.